Concentrated Growth Factor Matrices Prepared Using Silica-Coated Plastic Tubes Are Distinguishable From Those Prepared Using Glass Tubes in Platelet Distribution: Application of a Novel Near-Infrared Imaging-Based, Quantitative Technique - Yamaguchi, Sadahiro; Aizawa, Hachidai; Sato, Atsushi; Tsujino, Tetsuhiro; Isobe, Kazushige; Kitamura, Yutaka; Watanabe, Taisuke; Okudera, Hajime; Mourão, Carlos Fernando; Kawase, Tomoyuki (Frontiers in Bioengineering and Biotechnology, 2020)
Platelet-rich fibrin (PRF) matrices were originally prepared using plain glass tubes without the aid of coagulation factors because coagulation factor XII is activated by glass surfaces. Recently, the use of silica-coated plastic tubes as a substitute of glass tubes has been recommended for PRF preparation. This recommendation is owing not only to the shortage of glass tubes for medical use in the market, but also the higher coagulation activity of silica-coated plastic tubes and equal quality of PRF. However, these matrices are not the same. To evaluate the differences, we compared glass- and silica-coated plastic tubes in terms of platelet distribution and quantity in concentrated growth factors (CGF). CGF matrices were immediately prepared from freshly collected blood samples, fixed after red thrombus removal, and divided into two equal pieces sagittally. One piece was used for CD41 detection and the other was applied as an isotype control. Platelet distribution in CGF matrices was examined, without embedding or sectioning, by a novel method using invisible near-infrared imaging. The dehydrated membranous CGF matrix was more transparent. Thus, the fluorescence signal was clearly detectable with less scattering. Platelets were distributed mainly in the distal side of the glass-prepared CGF matrix, but homogeneously in the silica-prepared CGF matrix. Platelet count was positively correlated with fluorescence intensity. Although not yet fully developed, this imaging technique enabled us to recognize the differences in platelet distribution and quantity in CGF matrices by excluding bias caused by the technical limitations of scanning electron microscopy and conventional immunohistochemical methods.